2021
DOI: 10.1186/s40580-020-00252-5
|View full text |Cite
|
Sign up to set email alerts
|

PEO based polymer-ceramic hybrid solid electrolytes: a review

Abstract: Compared with traditional lead-acid batteries, nickel–cadmium batteries and nickel-hydrogen batteries, lithium-ion batteries (LIBs) are much more environmentally friendly and much higher energy density. Besides, LIBs own the characteristics of no memory effect, high charging and discharging rate, long cycle life and high energy conversion rate. Therefore, LIBs have been widely considered as the most promising power source for mobile devices. Commonly used LIBs contain carbonate based liquid electrolytes. Such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
121
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 174 publications
(123 citation statements)
references
References 95 publications
1
121
1
Order By: Relevance
“…PEO-based polymer electrolyte, on the other hand, has an issue with a dramatic fall in ionic conductivity at room temperature due to PEO crystallisation, even if it has a good ionic conductivity at temperatures above 60 °C. A variety of research groups reported using various methods to boost conductivity, such as adding inorganic fillers [5][6][7], gel electrolyte [8] and grafted polymers [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…PEO-based polymer electrolyte, on the other hand, has an issue with a dramatic fall in ionic conductivity at room temperature due to PEO crystallisation, even if it has a good ionic conductivity at temperatures above 60 °C. A variety of research groups reported using various methods to boost conductivity, such as adding inorganic fillers [5][6][7], gel electrolyte [8] and grafted polymers [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…By adding a certain substance to form a composite phase, and then controlling the proportion and distribution of the composite phase, new molecular structures and ion transport channels can be generated, which can improve the electrochemical performance of the SSEs (Zhang et al, 2018;Yu and Manthiram, 2021). So researchers have a great research interest in this new type of composite PSSEs (CPSSEs) (Bao et al, 2018;Li et al, 2020;Feng et al, 2021). Among many polymer systems, PEO-based is considered to be the most commonly used polymer substrate.…”
Section: Introductionmentioning
confidence: 99%
“…[ 38,39 ] However, the low oxidation potential of PEO (0–3.13 V) limits its practical application to solid‐state batteries. [ 38,40–43 ] Compared with PEO, polyacrylonitrile (PAN) has good thermal stability and mechanical properties. [ 44 ] In addition, the oxidation‐resistant PAN can accompany well with high‐potential cathode materials.…”
Section: Introductionmentioning
confidence: 99%